PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM PERUSAKAN LINGKUNGAN HIDUP - Gunawan, Lidya Pratiwi; Ratnawati Gultom, Elfrida (Universitas Ekasakti, 2023)
The goal of this research is to investigate and determine the regulation of environmental offenses under Law 32 of 2009(known as environmental law) and how to be responsible for environmental crimes according to environmental law This research uses normative legal research methods using primary and secondary data, with descriptive analysis and deductive conclusions. Environmental crimes can be include within intentional or unintentional acts. Subjects of criminal law may be individuals, legal bodies, or non-legal entities. In this scenario, both legal entities and non-legal entities are companies. Responsibility in Article 88 means 'absolute accountability,' or the so-called